TRANSFORMASI IDENTITAS DALAM ARSITEKTUR INTERIOR MASJID RAMLIE MUSOFA: SINERGI BUDAYA DAN SPIRITUALITAS: IDENTITY TRANSFORMATION IN THE ARCHITECTURE INTERIOR OF RAMLIE MUSOFA MOSQUE: A SYNERGY OF CULTURE AND SPIRITUALITY - Layla Nurina Kartika Iskandar; Siti Febrina Rahmadani; Rosalinda Wiemar; Ariani (Jurnal Seni dan Reka Rancang: Jurnal Ilmiah Magister Desain, 2026)
The Ramlie Musofa Mosque, located at Jalan Danau Sunter Selatan Blok I/10 No.12C-14A, North Jakarta, serves as a fascinating example of cultural acculturation in mosque architecture in Indonesia. The research titled "Identity Transformation in the Interior Architecture of Ramlie Musofa Mosque: A Synergy of Culture and Spirituality" aims to examine issues related to how Chinese architectural and interior elements within the mosque interact with Islamic cultural and spiritual values. The main problem addressed is the potential identity confusion of the mosque due to the blending of Chinese cultural symbols with Islamic values, which may influence the perceptions of the Muslim community. The purpose of this research is to understand the process of acculturation that occurs in the mosque’s architecture and how the fusion of cultures can either enhance or diminish the spiritual experience within the prayer space. The research objective is to analyze how non-Islamic cultural elements in the mosque’s architecture can still synergize with its primary function as a place of worship for Muslims. The benefit of this study is to provide new insights into cultural integration within Islamic architecture in Indonesia. The research method adopts a phenomenological approach through field observation analysis, interviews with congregants as well as the mosque's architect and interior designer, and literature reviews from social media sources and scholarly journals related to cultural acculturation and mosque architecture in Indonesia. This method enables the researcher to explore the meanings and subjective experiences of congregants who directly interact with a worship space rich in diverse cultural elements, offering insights into the impact of acculturation within the context of religious architecture in Indonesia. This research is expected to produce a scientific article published in an accredited national journal, as well as a research poster to be publicly presented, leading to the issuance of an Intellectual Property (HKI) Copyright Certificate.